Developing Point-of-Care Ultrasound Curricula for Internal Medicine Residency Programs: Consensus-Based Recommendations on Skills, Teaching Methods, and Evaluation Strategies - Chockalingam, Leela; Hammar, Dagan; Ortiz-Lopez, Carolina; Fleshner, Michelle; Keniston, Angela; McBeth, Lauren; Baduashvili, Amiran (Annals of internal medicine, 2025)
Despite growing adoption of point-of-care ultrasound (POCUS) education by internal medicine residency programs (IMRPs), there is no consensus on the specific skills that should be taught, the most effective teaching methods for content delivery, and the optimal strategies for evaluating trainees. To establish consensus among leaders in POCUS education on essential POCUS skills, preferred educational methods, and effective evaluation strategies for IMRPs. Modified 3-round Delphi panel. Online surveys conducted from 12 December 2023 to 5 May 2024. Persons who hold POCUS leadership positions at U.S.-based national internal medicine societies, teach at national or regional POCUS courses, or have a publication record in POCUS education. Participants ranked the importance of POCUS skills, teaching methods, and evaluation strategies on a 5-point Likert scale. Items that reached consensus, defined as IQR of 1 or less, were included if 70% or more respondents rated them as 4 or 5 or excluded if the median score was 1 or 2. Of the 36 invited persons, 21 (58%) participated. After 3 rounds, 53 of 103 (51%) POCUS skills, 14 of 35 (40%) teaching methods, and 5 of 9 (56%) evaluation strategies met consensus for inclusion. The included skills spanned lung (25%), abdominal (23%), procedural (23%), cardiac (17%), musculoskeletal (9%), and vascular (4%) domains. Applicability may be limited in resource-constrained and outpatient-focused training settings. This national consensus provides a detailed framework of POCUS skills, instructional methods, and assessment strategies considered essential by leaders in POCUS education. These findings can inform standardized curriculum development across IMRPs. None.